The Role and Design of a Transfer Pricing Risk Assessment Framework for Tax Administrators - Thi, T.; Mortimer, Colleen; Pinto, Dale (Taxation Institute of Australia, 2014)
Transfer pricing has become one of the most important contemporary international tax issues. Transfer pricing risk assessment is a critical issue for all tax administrations to identify the right cases to audit and subsequently impose an appropriate level of transfer pricing enforcement in the event of non-compliance with relevant transfer pricing rules. This article will provide an overview of transfer pricing issues and examine reasons why transfer pricing risk assessments play a significant role in tax administration. Based on the approach suggested by the Organisation for Economic and Co-operation and Development, a discussion of which factors should be considered when conducting transfer pricing risk assessment will be undertaken. A number of recommendations for designing procedures and methods for the assessment will also be made for developing countries drawing from the experience of developed countries where transfer pricing risk assessment procedures have already effectively been implemented.